An Experimental Liver Metastasis Mouse Model Suitable for Short and Long‐Term Intravital Imaging. Issue 5 (7th May 2021) - Marvin, Dieuwke L.; ten Dijke, Peter; Ritsma, Laila
Abstract: The liver is a frequent site of cancer metastasis, but current treatment options for cancer patients with liver metastasis are limited, resulting in poor prognosis. Colonization of the liver by cancer cells is a multistep and temporally controlled process. Investigating this process in biological relevant settings in a dynamic manner may lead to new therapeutic avenues. Experimental mouse models of liver metastasis combined with high‐resolution microscopy methods can facilitate study of the mechanisms that underlie the outgrowth of cancer cells in the liver. Intravital imaging can provide information on the behavior of tumor cells in their biological setting, in time frames of hours to days. In this unit, we describe the experimental induction of liver metastasis through administration of cancer cells into mice via mesenteric vein injection. The behavior of these injected cells can then be studied using intravital imaging by surgical exposure or through an abdominal imaging window. The approach is described for use with an upright multiphoton microscope, making it widely applicable. © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Inducing liver metastasis through mesenteric vein injection Basic Protocol 2 : Short‐term imaging of tumor cells in mouse liver Basic Protocol 3 : Long‐term imaging of tumor cells in mouse liver using an abdominal imaging window